The prospectivity of a potential shale gas play: An example from the southern Pennine Basin (central England, UK) - Hennissen, Jan A.I.; Hough, Edward; Vane, Christopher H.; Leng, Melanie J.; Kemp, Simon J.; Stephenson, Michael H. (Elsevier, 2017)
During the Serpukhovian (late Mississippian) Stage, the Pennine Basin, now underlying much of northern England, consisted of a series of interlinked sub-basins that developed in response to the crustal extension north of the Hercynic orogenic zone. For the current study, mudstone samples of the Morridge Formation from two sub-basins located in the south-eastern part of the Pennine Basin were collected from the Carsington Dam Reconstruction C3 Borehole (Widmerpool Gulf sub-basin) and the Karenight 1 Borehole (Edale Gulf sub-basin). Detailed palynological analyses indicate that aside from the dominant (often 90% or more) heterogeneous amorphous organic matter (AOM), variable abundances of homogeneous AOM and phytoclasts are present. To complement the palynological dataset, a suite of geochemical and mineralogical techniques were applied to evaluate the prospectivity of these potentially important source rocks. Changes in the carbon isotope composition of the bulk organic fraction (δ13COM) suggest that the lower part (Biozone E2a) of Carsington DR C3 is markedly more influenced by terrigenous kerogen than the upper part of the core (Biozones E2a3–E2b1). The Karenight 1 core yielded more marine kerogen in the lower part (Marine Bands E1–E2b) than the upper part (Marine Band E2b). Present day Rock-Eval™ Total Organic Carbon (TOC) surpasses 2% in most samples from both cores, a proportion suggested by Jarvie (2012) that defines prospective shale gas reservoirs. However, when the pyrolysable component that reflects the generative kerogen fraction is considered, very few samples reach this threshold. The kerogen typing permits for the first time the calculation of an original hydrogen index (HIo) and original total organic carbon (TOCo) for Carboniferous mudstones of the Pennine Basin. The most prospective part of Carsington DR C3 (marine bands E2b1–E2a3) has an average TOCo of 3.2% and an average HIo of 465 mg/g TOCo. The most prospective part of Karenight 1 (242.80–251.89 m) is characterized by an average TOCo of 9.3% and an average HIo of 504 mg/g TOCo. Lastly, X-ray diffraction (XRD) analysis confirms that the siliceous to argillaceous mudstones contain a highly variable carbonate content. The palynological, geochemical and mineralogical proxies combined indicate that marine sediments were continuously being deposited throughout the sampled intervals and were punctuated by episodic turbiditic events. The terrestrial material, originating from the Wales-Brabant High to the south of the Pennine Basin, was principally deposited in the Widmerpool Gulf, with much less terrigenous organic matter reaching the Edale Gulf. As a consequence, the prospective intervals are relatively thin, decimetre-to meter-scale, and further high resolution characterization of these intervals is required to understand variability in prospectivitiy over these limited intervals.